(3MRH GdHMQs - (3GdTGPdj, CHh GdMSf, fhQ GdOjf, Ydj Hf YHO Gddg Hf YHO GdLHGQ, J(B656(3g`s
(3ChdgG (B:s
(3jG Gddg jG Ydj jG YXje jG Mdje jG Ydje CfJ QHj Ydec MSHj JfUQ ef JTGA hCfJ GdYRjR GdQMjes
(3BNQgG (B:s
(3ceG OGQ HeOjfI GdfHj Udi Gddg Ydjg hSde SHMGf ef CdLe cd eJeQO LHGQ hjbgQg, hdG Mhd hdG bhI EdG HGddg GdYdj GdYXjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 305s
(3eYLe GdeDdajf(B: 2 / 467s
(3cTa GdXfhf(B: 1 / 661s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs